Synthesis and SAR development of quinoline analogs as novel P2X7 receptor antagonists. Issue 13 (1st July 2019) - Xiao, Yufang; Karra, Srinivasa; Goutopoulos, Andreas; Morse, Noune Tahmassian; Zhang, Susan; Dhanabal, Mohanraj; Tian, Hui; Seenisamy, Jeyaprakashnarayanan; Jayadevan, Jayashankaran; Caldwell, Richard; Potnick, Justin; Bleich, Matthew; et al.
Graphical abstract: Abstract: The P2X7 receptor (P2X7R) plays an important role in diverse conditions associated with tissue damage and inflammation, suggesting that the human P2X7R (hP2X7R) is an attractive therapeutic target. In the present study, the synthesis and structure-activity relationship (SAR) of a novel series of quinoline derivatives as P2X7R antagonists are described herein. These compounds exhibited mechanistic activity (YO PRO) in an engineered HEK293 expressing hP2X7R as well as a functional response (IL-1β) in human THP-1 (hTHP-1) cellular assays. Compound19 was identified as the most promising compound in this series with excellent cellular potency, low liver microsomal clearance, good permeability and low efflux ratio. In addition, this compound also displayed good pharmacokinetic properties and acceptable brain permeability (Kp, uu of 0.37).